Implementation of a Practical Teaching Course on Protein Engineering - Luciana C. Gomes (2022)
Simple Summary Proteins are the workhorses of the cell. With different combinations of the 20 common amino acids and some modifications of these amino acids, proteins have evolved with a staggering array of new functions and capabilities due to Protein Engineering techniques. The practical course presented was offered to undergraduate bioengineering and chemical students at the Faculty of Engineering of the University of Porto (Portugal) and consists of sequential laboratory sessions to learn the basic skills related to the expression and purification of recombinant proteins in bacterial hosts. These experiments were successfully applied by students as all working groups were able to isolate a model recombinant protein (the enhanced green fluorescent protein) from a cell lysate containing a mixture of proteins and other biomolecules produced by an Escherichia coli strain and evaluate the performance of the extraction and purification procedures they learned. Protein Engineering is a highly evolved field of engineering aimed at developing proteins for specific industrial, medical, and research applications. Here, we present a practical teaching course to demonstrate fundamental techniques used to express, purify and analyze a recombinant protein produced in Escherichia coli-the enhanced green fluorescent protein (eGFP). The methodologies used for eGFP production were introduced sequentially over six laboratory sessions and included (i) bacterial growth, (ii) sonication (for cell lysis), (iii) affinity chromatography and dialysis (for eGFP purification), (iv) bicinchoninic acid (BCA) and fluorometry assays for total protein and eGFP quantification, respectively, and (v) sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) for qualitative analysis. All groups were able to isolate the eGFP from the cell lysate with purity levels up to 72%. Additionally, a mass balance analysis performed by the students showed that eGFP yields up to 46% were achieved at the end of the purification process following the adopted procedures. A sensitivity analysis was performed to pinpoint the most critical steps of the downstream processing.